The Polarizing Effect of the Stimulus: Partisanship and Voter Responsiveness to the American Recovery and Reinvestment Act. Issue 2 (13th May 2016) - Einstein, Katherine Levine; Trump, Kris‐Stella; Williamson, Vanessa
Abstract : We examine the effect of a sudden influx of government spending, the 2009 American Recovery and Reinvestment Act (ARRA) on support for the president's party. Using a difference‐in‐differences design, we find that stimulus spending had a modest positive effect on Democratic vote share but only in counties that were already Democratic leaning. In Republican counties, by contrast, government spending had a small, but significant negative effect on Democratic vote share. That is to say, ARRA polarized already partisan places. These results have important implications for the study of voter responsiveness to government spending and the measurement of the political effects of policy visibility.